2019
DOI: 10.1186/s12934-019-1263-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined artificial high-silicate medium and LED illumination promote carotenoid accumulation in the marine diatom Phaeodactylum tricornutum

Abstract: BackgroundDiatoms, which can accumulate large amounts of carotenoids, are a major group of microalgae and the dominant primary producer in marine environments. Phaeodactylum tricornutum, a model diatom species, acquires little silicon for its growth although silicon is known to contribute to gene regulation and play an important role in diatom intracellular metabolism. In this study, we explored the effects of artificial high-silicate medium (i.e. 3.0 mM sodium metasilicate) and LED illumination conditions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…In addition, our results confirm observations from another study on the impact of red light where biomass increased by 40% under enriched red light [40]. Similarly, another study reported better growth and higher fucoxanthin content in P. tricornutum under red and blue light [30]. That study is similar to our treatment RS, where we have supplied a red wavelength for the first 7 days and then exposed the culture to the white light during the stationary phase.…”
Section: Analysis Of Total Biomass and Lipid Content Under Red Light supporting
confidence: 91%
See 4 more Smart Citations
“…In addition, our results confirm observations from another study on the impact of red light where biomass increased by 40% under enriched red light [40]. Similarly, another study reported better growth and higher fucoxanthin content in P. tricornutum under red and blue light [30]. That study is similar to our treatment RS, where we have supplied a red wavelength for the first 7 days and then exposed the culture to the white light during the stationary phase.…”
Section: Analysis Of Total Biomass and Lipid Content Under Red Light supporting
confidence: 91%
“…Indeed, at day 11, the RS growth was significantly higher with 22% and 14% more cells than continuous W and R light, respectively ( Figure 2). The cell growth observed under R and RS treatment can be explained, in part, by the presence of a wide range of photoreceptors with the ability to sense red/far-red wavelengths and their potential to prevent photoinhibition [30,32]. A similar study has reported the increasing growth of P. tricornutum under defined and efficient combinations of red and blue lights [30].…”
Section: Growth Curve Analysis Of P Tricornutum During Red Light Shiftmentioning
confidence: 89%
See 3 more Smart Citations